Pain Catastrophizing and Arthritis Self-Efficacy as Mediators of Sleep Disturbance and Osteoarthritis Symptom Severity. Issue 3 (22nd August 2019) - Tighe, Caitlan A; Youk, Ada; Ibrahim, Said A; Weiner, Debra K; Vina, Ernest R; Kwoh, C Kent; Gallagher, Rollin M; Bramoweth, Adam D; Hausmann, Leslie R M
Abstract: Objective: Sleep and pain-related experiences are consistently associated, but the pathways linking these experiences are not well understood. We evaluated whether pain catastrophizing and arthritis self-efficacy mediate the association between sleep disturbance and osteoarthritis (OA) symptom severity in patients with knee OA. Methods: We analyzed cross-sectional baseline data collected from Veterans Affairs (VA) patients enrolled in a clinical trial examining the effectiveness of a positive psychology intervention in managing pain from knee OA. Participants indicated how often in the past two weeks they were bothered by trouble falling asleep, staying asleep, or sleeping too much. We used validated scales to assess the primary outcome (OA symptom severity) and potential mediators (arthritis self-efficacy and pain catastrophizing). To test the proposed mediation model, we used parallel multiple mediation analyses with bootstrapping, controlling for sociodemographic and clinical characteristics with bivariate associations with OA symptom severity. Results: The sample included 517 patients (Mage = 64 years, 72.9% male, 52.2% African American). On average, participants reported experiencing sleep disturbance at least several days in the past two weeks (M = 1.41, SD = 1.18) and reported moderate OA symptom severity (M = 48.22, SD = 16.36). More frequent sleep disturbance was associated with higher OA symptom severity directly ( b = 3.08, P <0.001) and indirectly, through higher pain catastrophizing ( b = 0.60, 95% confidence interval [CI] = 0.20 to 1.11) and lower arthritis self-efficacy ( b = 0.84, 95% CI = 0.42 to 1.42). Conclusions: Pain catastrophizing and arthritis self-efficacy partially mediated the association between sleep disturbance and OA symptom severity. Behavioral interventions that address pain catastrophizing and/or self-efficacy may buffer the association between sleep disturbance and OA symptom severity.